Determining physical and mechanical volcanic rock properties via reflectance spectroscopy - Schaefer LN; Kereszturi G; Villeneuve M; Kennedy B (Elsevier B V, 2021)
There are currently no reliable methods to determine rock physical and mechanical properties that are not labor or resource intensive, especially at the scale of volcanoes. Using mineralogical-physical-mechanical relationships, we suggest it is possible to derive rock properties from rapid, non-invasive reflectance spectroscopy measurements. To demonstrate this potential, we correlate the physical and mechanical properties of variously altered andesitic volcanic rocks to laboratory reflectance spectroscopy using statistical analysis. Several rock properties, including density, connected porosity, strength, magnetic susceptibility, and elasticity, correlate with reflectance spectroscopy in both the visible and short-wave infrared parts of the electromagnetic spectrum. We attribute these correlations to the presence and degradation (i.e. weathering or hydrothermal alteration) of iron-bearing minerals such as pyroxene, magnetite, and pyrite, which reflect changes to both rock properties and reflectance spectroscopy measurements. Results support the use of transfer functions to estimate rock properties directly from reflectance spectroscopy. Ultimately, aerial or satellite imaging spectroscopy could be used to create geotechnical maps at volcano scale
Keywords: Transfer function; Andesite; Hydrothermal alteration; Weathering; Iron-bearing mineral phases; Clay; Short wave infrared; Visible spectrum; Reflectance spectroscopy